Single-center, prospective study evaluating safety and efficacy of a new endoscopic hemostat system in non-variceal upper gastrointestinal bleeding - Rughwani, Hardik; Garg, Rajat; Habeeb, Mohammed Faisal; Jagtap, Nitin; Nabi, Zaheer; Inavolu, Pradev; Aachi, Shreevyshnavi; Ramchandani, Mohan; Santosh, Darisetty; Nayak, Gauri; Lakhtakia, Sundeep; Reddy, Nageshwar (Endoscopy International Open, 2025)
Endoscopic spray therapy has been shown to be effective and safe in managing upper gastrointestinal bleeding (UGIB). We aimed to evaluate safety and efficacy of the novel powder-based Resolv Endoscopic Hemostat System in managing UGIB.This was a single-center, prospective, single-arm study conducted from July 2022 to February 2023. It aimed to evaluate safety and efficacy of a novel plant-based polysaccharide, the Resolv Endoscopic Hemostat System, in achieving hemostasis in adult patients diagnosed with non-variceal upper gastrointestinal bleeding (UGIB) (Forest 1b/oozing bleeding). Participants in this study underwent endoscopy and received monotherapy treatment using the Resolv Endoscopic Hemostat System. Outcomes of interest were adverse events (AEs) related to the device within 72 hours and 30 days, immediate hemostasis, and rebleeding rates within 72 hours of the index procedure.A total of 59 patients (71.2% men) with mean age of 55.3 ± 14.2 years were included in the study. Causes of bleeding included post-polypectomy (n = 35, 59.3%), gastric ulcers (n = 13, 22%), malignant tumor (n = 4, 6.8%), post-biopsy-related needing hemostasis (n = 3, 5.1%), congestive gastropathy (n = 2, 3.4%), duodenal ulcer (n = 1, 1.7%), and portal hypertensive duodenopathy-related (n = 1, 1.7%). Resolv achieved a 100% success rate for immediate hemostasis with a 72-hour rebleeding rate of 5.1%. There were no AEs related to the device or mortality.Resolv Endoscopic Hemostat System is a safe and effective device for achieving immediate hemostasis in patients with non-variceal upper gastrointestinal bleeding. Future studies are required to examine its widespread adoption and applicability.
Keywords: Endoscopy Upper GI Tract; Non-variceal bleeding; Ulcers (peptic and other); Endoscopy Small Bowel; Small intestinal bleeding